TRANSFORMATION OF GREEN UNIVERSITIES IN INDONESIA: THE ROLE OF TRANSFORMATION LEADERSHIP STYLE INNOVATION AND GREEN MANAGEMENT ACCOUNTING IN ACHIEVING SUSTAINABILITY PERFOMANCE - Richard Andrew; Lusy Lusy; Yosef Pranata (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
In the era of smart society 5.0, universities are required not only to excel academically, but also to be able to demonstrate sustainability performance that includes economic, social, and environmental aspects. Catholic University as an institution based on values and spirituality has a strategic role in addressing global sustainability challenges. The urgency of this research lies in the need for a deeper understanding for the entire academic community on how the application of transformational leadership style and Green management accounting can encourage the achievement of sustainability performance in the environment of universities in Indonesia, the level of application and understanding is still diverse in the achievement of sustainability performance. The object of research is all universities in Surabaya and Jakarta, because they are the two largest cities in Indonesia and become the mecca of tridarma of higher education throughout Indonesia. The main purpose of this study was to analyze and examine the influence of transformational leadership style and Green management accounting on the sustainability performance of universities in Indonesia. Specific objectives, this study wants to uncover the strategic role of green Management Accounting in maintaining the sustainability of institutions in the midst of technological developments and global environmental demands. The study used a quantitative approach with survey methods. The Data was collected through a Likert scale 1-5 questionnaire distributed via google form to the academic community of selected universities in Jakarta and Surabaya. Sampling technique using purposive sampling. Data analysis was conducted to test the relationship between variables and draw empirical conclusions.